ADUBAÇÃO FOLIAR DO FEIJOEIRO (Phaseolus vulgaris L.): III. EFEITOS DE NP E NPK - Balducci Jr., J. J.; Rosolem, C. A.; Machado, J. R. (REVISTA DE AGRICULTURA, 2015)
ADUBAÇÃO FOLIAR DO FEIJOEIRO (Phaseolus vulgaris L.): III. EFEITOS DE NP E NPK